ANKRD26 recruits PIDD1 to centriolar distal appendages to activate the PIDDosome following centrosome amplification. (22nd December 2020) - Evans, Lauren T; Anglen, Taylor; Scott, Phillip; Lukasik, Kimberly; Loncarek, Jadranka; Holland, Andrew J
Abstract: Centriole copy number is tightly maintained by the once‐per‐cycle duplication of these organelles. Centrioles constitute the core of centrosomes, which organize the microtubule cytoskeleton and form the poles of the mitotic spindle. Centrosome amplification is frequently observed in tumors, where it promotes aneuploidy and contributes to invasive phenotypes. In non‐transformed cells, centrosome amplification triggers PIDDosome activation as a protective response to inhibit cell proliferation, but how extra centrosomes activate the PIDDosome remains unclear. Using a genome‐wide screen, we identify centriole distal appendages as critical for PIDDosome activation in cells with extra centrosomes. The distal appendage protein ANKRD26 is found to interact with and recruit the PIDDosome component PIDD1 to centriole distal appendages, and this interaction is required for PIDDosome activation following centrosome amplification. Furthermore, a recurrent ANKRD26 mutation found in human tumors disrupts PIDD1 localization and PIDDosome activation in cells with extra centrosomes. Our data support a model in which ANKRD26 initiates a centriole‐derived signal to limit cell proliferation in response to centrosome amplification. SYNOPSIS: Centrosome amplification contributes to tumorigenesis, but in non‐transformed cells activates the PIDDosome to inhibit cell proliferation. A genome‐wide screen identifies the centriolar distal appendage protein ANKRD26 as PIDD1 recruiter and PIDDosome activator in such situations. ANKRD26 recruits the PIDDosome component PIDD1 to centriole distal appendages. Centriolar recruitment of PIDD1 is required for PIDDosome activation following centrosome amplification. A cancer‐linked ANKRD26 mutation disrupts PIDD1 centriolar recruitment and PIDDosome activation in cells with extra centrosomes. ANKRD26 initiates a centriole‐derived signal to limit cell proliferation following centrosome amplification. Abstract : A genome‐wide screen identifies a key role for distal appendage protein ANKRD26 in cell proliferation inhibition in the presence of extra‐centrosomes, which is affected by cancer‐linked mutations.